2009
DOI: 10.1016/j.neuint.2009.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Early long-term exposure with caffeine induces cross-sensitization to methylphenidate with involvement of DARPP-32 in adulthood of rats

Abstract: Chronic ingestion of caffeine causes dependence and sleep disturbance in children and adolescents. In rodents, the administration of caffeine may produce behavioral cross-sensitization to some psychostimulants, such as dopaminergic psychoactive drugs. Methylphenidate (MPH; Ritalin) is a psychostimulant used in pediatric- and adult human populations to manage the symptoms associated with attention-deficit hyperactivity disorder (ADHD). Previous studies have suggested that dopamine- and cAMP-regulated phosphopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
2
12
0
2
Order By: Relevance
“…The increases in total DARPP-32 expression in the NAc also suggest increased dopamine signaling in the NAc that is associated with heightened sensitivity and reward to cocaine (Fienberg et al, 1998;Zachariou et al, 2002). This finding corroborates with a recent study where adolescent caffeine exposure increased both methylphenidate-induced locomotion and total DARPP-32 expression (Boeck et al, 2009). Together, these findings suggest that chronic caffeine consumption during adolescence enhances dopamine receptor signaling in the NAc.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The increases in total DARPP-32 expression in the NAc also suggest increased dopamine signaling in the NAc that is associated with heightened sensitivity and reward to cocaine (Fienberg et al, 1998;Zachariou et al, 2002). This finding corroborates with a recent study where adolescent caffeine exposure increased both methylphenidate-induced locomotion and total DARPP-32 expression (Boeck et al, 2009). Together, these findings suggest that chronic caffeine consumption during adolescence enhances dopamine receptor signaling in the NAc.…”
Section: Discussionsupporting
confidence: 89%
“…Chronic caffeine consumption produces tolerance to caffeine to a greater extent in adolescents compared with adults, suggesting that adolescent animals may exhibit greater brain changes associated with chronic caffeine consumption (Rhoads et al, 2011). Chronic caffeine exposure in adolescents also produces behavioral cross-sensitization with methylphenidate when tested in adulthood in the absence of caffeine (Boeck et al, 2009). Given the differences in sensitivity and susceptibility adolescents display to the behavioral changes produced by chronic caffeine exposure, we hypothesized that caffeine consumption during adolescence may enhance the behavioral sensitivity to cocaine by producing changes in protein expression and dopamine release within the NAc.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports provide evidence alleging that treatment with MPD protects youths from substance abuse later in life [6,76]. In rats, it has also been shown that long-term exposure to caffeine during adolescence induces cross-sensitization to MPD during adulthood [7]. Past data suggests that the inconsistencies in these findings have resulted from a variety of factors, including differences in drug dosage, route of administration, time of administration, age, gender, and animal model used [3,4,20,80].…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary dose analysis indicated that higher concentrations of caffeine were not well tolerated. Bottles were changed every 2-3 days as described previously (Boeck et al, 2009; da Silva et al, 2003). …”
Section: Methodsmentioning
confidence: 99%